Intracerebroventricular administration of streptozotocin causes long-term diminutions in learning and memory abilities and in cerebral energy metabolism in adult rats - Lannert, Heinrich; Hoyer, Siegfried (Behavioral neuroscience, 1998)
Drastic abnormalities have been demonstrated to occur in cerebral glucose and energy metabolism in sporadic Alzheimer's disease, pointing to a primary disturbance in neuronal insulin and insulin receptor signal transduction and contributing to the causation of dementia. The compound streptozotocin (STZ) is known to inhibit insulin receptor function. This study was designed to investigate whether intracerebroventricularly (icv) applied STZ would inhibit neuronal insulin receptor function and would induce changes in both behavior and neuronal energy metabolism. Adult rats with icv-injected STZ developed long-term and progressive deficits in learning, memory, and cognitive behavior, indicated by decreases in working and reference memory in the holeboard task and the passive avoidance paradigm, along with a permanent and ongoing cerebral energy deficit. This animal model may be appropriate for investigations related to sporadic Alzheimer's dementia. (PsycInfo Database Record (c) 2025 APA, all rights reserved)